Determinants of the Choice of Migration Destination. - Fafchamps, M; Shilpi, F (Blackwell Publishing, 2012)
This paper examines migrants’ choice of destination conditional on migration. The study uses data from two rounds of Nepal Living Standard Surveys and a Population Census and examine how the choice of a migration destination is influenced by various covariates, including income differentials across possible destinations. We find that migrants move primarily to nearby, high population density areas where many people share their language and ethnic background. Better access to amenities is significant as well. Differentials in average income across destination districts are significant in univariate comparisons but not once we control for other covariates. Differentials in consumption expenditures are statistically significant but smaller in magnitude than other determinants. It is differentials in absolute, not relative, consumption between destination districts that are correlated with the destination of work migrants. Except for the latter, results are robust to different specifications and datasets.